2011
DOI: 10.1111/j.1474-9726.2011.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Sir2 deletion prevents lifespan extension in 32 long‐lived mutants

Abstract: SUMMARY Activation of Sir2-orthologs is proposed to increase lifespan downstream of dietary restriction (DR). Here we describe an examination of the effect of 32 different lifespan-extending mutations and four methods of dietary restriction on replicative lifespan (RLS) in the short-lived sir2Δ yeast strain. In every case, deletion of SIR2 prevented RLS extension; however, RLS extension was restored when both SIR2 and FOB1 were deleted in several cases, demonstrating that SIR2 is not directly required for RLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 15 publications
3
38
1
Order By: Relevance
“…Yeast mother cells with an extra copy of the Sir2 gene show increases in replicative life span by up to 30%, whereas its deletion or mutation decreases their life span by 50% 10 . This role of Sir2 in life span extension is reproduced by many studies 11,12 . Moreover, another recent study that uses quantitative trait locus (QTL) analysis to investigate natural genetic variations associated with longevity in S. cerevisiae further demonstrates that Sir2 plays a critical role in longevity regulation in this organism 13 .…”
Section: Mammalian Sirtuinssupporting
confidence: 63%
“…Yeast mother cells with an extra copy of the Sir2 gene show increases in replicative life span by up to 30%, whereas its deletion or mutation decreases their life span by 50% 10 . This role of Sir2 in life span extension is reproduced by many studies 11,12 . Moreover, another recent study that uses quantitative trait locus (QTL) analysis to investigate natural genetic variations associated with longevity in S. cerevisiae further demonstrates that Sir2 plays a critical role in longevity regulation in this organism 13 .…”
Section: Mammalian Sirtuinssupporting
confidence: 63%
“…However, this finding is difficult to interpret. Whereas loss of SIR2 may indeed be epistatic to loss of SGF73 and UBP8 , more often we have found that longevity interventions that fail to extend RLS in the sir2Δ background retain their ability to do so in sir2 Δ fob1Δ strains ( Delaney et al, 2011; Kaeberlein et al, 2004) , which have a RLS similar to wild-type strains, most likely due to the suppressive effect of fob1Δ on ERC formation (Defossez et al, 1999; Kaeberlein et al, 1999b). Thus it was possible that sgf73Δ and ubp8Δ strains would be long-lived in a sir2Δ fob1Δ background.…”
Section: Resultsmentioning
confidence: 88%
“…Prior studies have shown that DR fails to increase the RLS of sir2Δ single mutant cells lacking the Sir2 histone deacetylase, but robustly increases the RLS of sir2Δ fob1Δ double mutant cells (Delaney et al, 2011b; Kaeberlein et al, 2004; Lin et al, 2000). Similarly, deletion of LOS1 did not increase the RLS of sir2Δ cells, but significantly increased the RLS of sir2Δ fob1Δ cells (p<0.001, Figure 3F, G) .…”
Section: Resultsmentioning
confidence: 97%